2019
DOI: 10.1016/j.aquaculture.2019.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Short-term lecithin enrichments can enhance the phospholipid and DHA contents of the polar lipid fraction of Artemia nauplii

Abstract: Wild copepods are the main natural diet of marine finfish and they meet the larvae's requirements in phospholipids and essential fatty acids (EFA). While Artemia nauplii are an easier and more reliable live feed to produce in hatcheries for marine fish larvae than wild zooplankton, enrichment products commercially used lack phospholipids and essential longchain polyunsaturated fatty acids (LC-PUFA). This is particularly true for docosahexaenoic acid (DHA) within their polar lipid fraction (PLDHA), which is cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
(62 reference statements)
2
6
0
Order By: Relevance
“…Nauplii from SP12 treatment contained, in addition to 4.2 mg Se kg -1 , markedly higher levels of essential fatty acids such as DHA (18.0 ± 1.1 %). This data is consistent with an Artemia enrichment study that showed the high efficiency of Larviva Multigain at supplying DHA, in which levels of 21.8 ± 0.7 % DHA postenrichment were obtained (Cavrois-Rogacki et al, 2019). Furthermore, none of the treatments with Sel-Plex significantly affected the levels of essential fatty acids (i.e.…”
Section: Discussionsupporting
confidence: 90%
“…Nauplii from SP12 treatment contained, in addition to 4.2 mg Se kg -1 , markedly higher levels of essential fatty acids such as DHA (18.0 ± 1.1 %). This data is consistent with an Artemia enrichment study that showed the high efficiency of Larviva Multigain at supplying DHA, in which levels of 21.8 ± 0.7 % DHA postenrichment were obtained (Cavrois-Rogacki et al, 2019). Furthermore, none of the treatments with Sel-Plex significantly affected the levels of essential fatty acids (i.e.…”
Section: Discussionsupporting
confidence: 90%
“…n−3/n-6 4.0 ± 0.1 2.6 ± 0.1 2.6 ± 0.1 2.1 ± 0.4 2.6 ± 0.1 2.6 ± 0.3 2.2 ± 0.4 DHA/EPA 6.2 ± 0.4 20.3 ± 1.0d 11.5 ± 0.5b 5.1± 0.2a 16.5 ± 0.9c 10.7 ± 0.7b 5.4 ± 1.2a The use of commercial enrichers for 12 h followed by the addition of marine phospholipids (LC60) using a short-term enrichment of 3 h was effective for that in the case of rotifers, as it has been shown by other authors (Olsen et al, 2014;Li and Olsen, 2015;Mylonas et al, 2016). In the case of Artemia a recent paper published by Rogacki et al (2019) showed that a certain amount of PLs can be obtained using Multigain as enricher and LC60 as the phospholipid source, similarly to our results, and open the possibility of using this PL-enriched Artemia in the future. Olsen et al (2014) and Li et al (2014) obtained a level of 9.4% of DHA (in % total fatty acids) in the PL fraction of the rotifers enriched with Marol E and suggested that this low level might be genetically or metabolically constrained.…”
supporting
confidence: 88%
“…On the other hand, copepods, the live prey that the larvae feed in the wild, are rich in phospholipids and in n−3 PUFA. Although the content of PL per dry weight (DW) of rotifers and Artemia cannot be manipulated, the fatty acid composition of PL can be modified in some degree (Guinot et al, 2013;Li et al, 2014;Rogacki et al, 2019). Supplementation of PL is usually carried out using commercial lecithin, either obtained from plants (soybean), chicken eggs, or pure phospholipids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rotifers and brine shrimps are the most commonly used live feeds in aquaculture, given relatively low-cost protocols for fixed batch production (Conceição et al 2010). Artemia enrichment has long been applied in hatcheries all over the world for enhancing the nutritional value of Artemia with essential fatty acids (Van Stappen 1996;McEvoy et al 1997;Agh and Sorgeloos 2005;Rogacki et al 2019). Nevertheless, their suitability as a diet for marine larvae is often questioned because of their relatively low phospholipid content compared with natural prey.…”
Section: Introductionmentioning
confidence: 99%